Bullets and bolos fifteen years in the Philippine Islands - White, John Roberts 1879- (New York Manila The Century Co. Felta Multi-Media Center, 2008)
"The account of thirteen years in the Philippine constabulary by one who was one of its most gallant and outstanding officers."--Foreword.
Distributed by FELTA Multi-Media.
"First printing, July, 1928."
This is an exact reproduction in PDF file of the original edition.
Keywords: Police -- Philippines; Philippines; Philippines -- Description and travel